Targeted expression of the immunomodulatory peptide Scy by engineered Escherichia coli Nissle 1917 for alleviating enterotoxigenic E. coli infection - Fu, Jie; Zhou, Lutong; Jiang, Xiao; Zhang, Hong; Chen, Yanli; Qiao, Lei; Song, Deguang; Lu, Zeqing; Wang, Tenghao; Jin, Mingliang; Zhang, Caiqiao; Wang, Yizhen; et al. (Frontiers in Immunology, 2026)
Oral delivery of functional small peptides holds great promise for the prevention and treatment of intestinal diseases. However, their clinical application is limited by rapid degradation in the gastrointestinal tract, low bioavailability, and poor targeting capacity. To address these challenges, we engineered the probiotic Escherichia coli Nissle 1917 to express the immunomodulatory peptide Scy (EcN-Scy) under the control of the anaerobically responsive pNirB promoter, thereby enabling site-specific expression in the hypoxic intestinal environment. In vitro experiments demonstrated that EcN-Scy exhibited stable peptide expression and strong tolerance to heat, acid, bile salts, and simulated gastrointestinal fluids. In vivo, EcN-Scy administration caused no organ toxicity or metabolic abnormalities in mice, but significantly enhanced colonic antioxidant capacity, corrected the imbalance of Th1/Th2 cytokines, and maintained local immune homeostasis. 16S rDNA sequencing revealed that EcN-Scy reshaped the gut microbiota structure by increasing the abundance of beneficial genera such as Parabacteroides, while suppressing the proliferation of opportunistic pathogens including Alistipes and Muribaculaceae. In the enterotoxigenic Escherichia coli (ETEC) K88 infection model, EcN-Scy significantly alleviated diarrheal symptoms and colonic mucosal injury, enhanced the expression of barrier-associated proteins, and suppressed pro-inflammatory cytokine release in the gut. Compared with wild-type EcN, EcN-Scy exhibited markedly superior effects in anti-inflammatory, anti-infective, and barrier-protective functions. Collectively, EcN-Scy represents a novel peptide-producing engineered probiotic capable of targeted intestinal delivery and localized immune modulation, offering substantial potential as an oral microecological therapeutic for the management of intestinal inflammation and pathogen-induced infections.